STUDI POLA OPERASI DAN KONSUMSI ENERGI POMPA KOLAM RENANG DI HOTEL RAMADA CAMAKILA DAN RAMADA BINTANG - Ginarsa, I Gede; Satya kumara, I N.; Ibi Weking, A. (Jurnal SPEKTRUM; Vol 5 No 1 (2018): Jurnal SPEKTRUMDO - 10.24843/SPEKTRUM.2018.v05.i01.p14, 2018)
The Ramada Bintang and Ramada Camakila hotels have pools of nearly equal water, but these two pools have different pumping and pumping systems. Ramada Bintang uses two pumps 5 Pk works 12 hours while Ramada Camakila uses two pumps 1.5 Pk work 24 hours, the condition of both pools have the same clarity and water quality. In this study, electrical energy measurements were performed on each pump and calculated chlorine, ph and number of people taking bath in each swimming pool. The average electricity consumption per day on the Ramada Bintang hotel pumping system is Rp. 106,080 while Ramada Camakila Rp. 74,640, so the difference in electricity consumption for a year in both hotels is Rp. 10,579. 068 with the same water quality ratio.